Effectiveness of Emotional Schema Therapy on Marital Intimacy among Couples on the Brink of Divorce - Amin Asgari; Kourosh Goodarzi (Shahid Beheshti University of Medical Sciences, 2019)
Background and Objective: Reduced marital intimacy disrupts family function, durability and sustainability of marriage. Low intimacy leads to a rise in inappropriate interactions, reduced satisfaction and happiness in marriage, and leads to a desire to get a divorce among couples. Therefore, the present study aimed to define the effect of emotional schema therapy on marital intimacy among couples on the brink of divorce. Materials and Methods: This study was of semi-experimental design with pre-test, post-test, follow-up and control group. Among all couples at the Justice Department in cities of Shahin Shahr and Meymeh in 2017 and applied for a divorce, 54 couples who had a standard deviation below the average of Bagarozzi's marital intimacy questionnaire, were selected by purposeful sampling method, and randomly divided into three groups: experimental, consulting and control. Then, the experimental group participated in the emotional schema therapy and the counulting group in the public conversation course. One month after the completion of the training courses, the groups completed the questionnaire by post-test and three months later they completed the questionnaire again. Data were analyzed by SPSS-22 using single and multivariate analysis of covariance. Results: Emotional schema therapy increased the mean (SD) of total marital intimacy of couples in the experimental group from 243.8 (57.7) in pre-test to 296.3 (63.5) in post-test and 306.9 (63.4) in follow-up (P<0.05). The effect of the emotional schema therapy on components in post-test was 56.6% for physical intimacy, 40.6% mental intimacy, 38.4% emotional intimacy, 43.2% psycological intimacy, 31.1% sexual intimacy, 27.7% spiritual intimacy, 26.2% scio-creational intimacy, 25% choronological intimacy, and 68.1% aesthetic intimacy. The effect of the emotional schema therapy in follow-up was 68.1% for physical intimacy, 61.3% spiritual intimacy, 60.4% scio-creational intimacy, 51.2% psycological intimacy, 49.5% emotional intimacy, 49.3% mental intimacy, 49.3% sexual intimacy, 48.5% choronological intimacy, and 45.4% aesthetic intimacy (P<0.05). In addition, there was a significant difference between the increase in the scores of marital intimacy and all its components among the couples of the cosulting group compared to the control group (P<0.05), but there was no significant difference between the two groups in the follow-up. Conclusion: The study showed that emotional schema therapy resulted in increased marital intimacy of couples on the brink of divorce.   DOI: http://doi.org/10.22037/ch.v6i2.23281